Effect of Media And Handling of Seed on Growth of Nyamplung (Calopyllum inophylum) Seedling - Suryawan, Ady (Balai Penelitian Kehutanan Manado, 2014)
This research aims to investigate the influence of media (topsoil and cocopeat) and seed treatment (control, immersion, cracking, and stripping) on the growth of nyamplung seeds from Talise Island on 3 months old. This research using Completely randomized design method with observations viability, height, diameter, robustness seedlings and seed quality index.Â Results of tests known that character nyamplung growth is influenced by the media and seed handling. Cocopeat media will improveÂ the viability but debase of growth, so that the necessary weaning with a more fertile medium. Handling seed by stripping the shell has a good influence on the growth and quality of seeds. Based on research, nyamplung requiring scarification with cocopeat media and stripping the shell.